2009
DOI: 10.5194/angeo-27-1775-2009
|View full text |Cite
|
Sign up to set email alerts
|

Space weather events in July 1982 and October 2003 and the effects of geomagnetically induced currents on Swedish technical systems

Abstract: Abstract. In this paper, we analyse in detail two famous space weather events; a railway problem on 13–14 July 1982 and a power blackout on 30 October 2003. Both occurred in Sweden during very intensive space weather storms and each of them a few years after the sunspot maximum. This paper provides a description of the conditions on the Sun and in the solar wind leading to the two GIC events on the ground. By applying modelling techniques introduced and developed in our previous paper, we also calculate the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(146 citation statements)
references
References 31 publications
2
133
1
3
Order By: Relevance
“…Several studies have been made for the Finnish high-voltage power grid (Pirjola 1989;Elovaara et al 1992;Mäkinen 1993) and the natural gas pipeline (Pulkkinen et al 2001a;Viljanen et al 2006). Sweden: Wik et al (2008) performed a statistical study of GIC in South Sweden, and Wik et al (2009) and Pulkkinen et al (2005) considered the most extreme GIC events observed in Sweden in July 1982 and October 2003. United Kingdom: Thomson et al (2005) modelled GIC during the extreme storm of October 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been made for the Finnish high-voltage power grid (Pirjola 1989;Elovaara et al 1992;Mäkinen 1993) and the natural gas pipeline (Pulkkinen et al 2001a;Viljanen et al 2006). Sweden: Wik et al (2008) performed a statistical study of GIC in South Sweden, and Wik et al (2009) and Pulkkinen et al (2005) considered the most extreme GIC events observed in Sweden in July 1982 and October 2003. United Kingdom: Thomson et al (2005) modelled GIC during the extreme storm of October 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Predictions of the strength and time variations of magnetic substorms have not yet reached a mature level for practical applications although post-event analyses have reached a high level of accuracy (e.g., Wik et al 2008Wik et al , 2009. General warnings of magnetic storm conditions following solar outbursts (CMEs) are provided by satellite data.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases the management of the power grid by the Swedish power company, ''Vattenfallet'', prevented further adverse consequences of the high-voltage power line cuts. The effects on consumers in Sweden were small and no effects were recorded in the coupled power grids in the neighboring countries, Finland, Norway, and Denmark during these storms (e.g., Stauning 2001;Stauning & Watermann 2002;Wik et al 2008Wik et al , 2009). …”
Section: Power Grid Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Large GIC are usually considered to occur at high latitudes such as North America and Scandinavia, where tripping problems and even blackouts of power systems due to GIC have been experienced (Bolduc 2002;Pulkkinen et al 2005;Wik et al 2009). Large currents in transformer neutrals have been monitored in the Chinese high-voltage power system many times during geomagnetic storms although China is a midlow-latitude country.…”
Section: Introductionmentioning
confidence: 99%